FASAHATUL KALAM: TANAFURIL AL-KALIMAT, DHU’FI AL-TA’LIF, DAN TA’QIDU SALIM - M. Choiril Annas; Uchie Syahmira Manurung; Ahmad Fadly Rahman (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
This study aims to demonstrate that the beauty of a text lies in the fluency of its sentences. The research method employed is descriptive qualitative research. Meanwhile, data collection was conducted through a review of books and journals. The results of the study indicate that to construct an eloquent sentence, it must be free from three aspects: tanafur kalimat, dhu’fu ta’lif, and ta’qidu salim. Furthermore, the Quran serves as the central focus of study regarding fasohatul kalam. The linguistic aesthetics and high level of balagha found within it make it visually appealing and difficult to imitate.